Water Engineering in Ancient Societies - Ortloff, Charles R. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The chapter 'Water Engineering in Ancient Societies' involves the use of modern hydraulic engineering principles to describe the design, construction and use of ancient World Heritage water-system structures in South America and the Middle East.